An approach of using polymer natural fiber composite for vibration and flammability control - Abd Karim, Muhammad Aizat (2018)
Recently the development of natural fiber composite instead of synthetics fiber has lead to eco-friendly product manufacturing to meet various applications in the field of automotive, construction and manufacturing. In this present research, the effects of maleic anhydride polypropylene (MAPP) on the material characterization behaviour, mechanical properties, vibration damping properties and flammability properties of kenaf fiber and coir fiber reinforced polypropylene were investigated. Different fractions of composites with 10wt%-40wt% coir fiber (CF) and kenaf fiber (KF) content were prepared by using brabender mixer at 190 °C. The 3wt% MAPP was added during the mixing. The composites were subsequently fabricated with injection molding and hydraulic hot press to prepare the test specimens. The effect of MAPP on morphology, mechanical properties, physical properties, vibration damping properties and flammability properties of CF or KF composites were then investigated by using FTIR, SEM, tensile test, density test, transmissibility test and vertical flame test, respectively. The results revealed that the 30wt% modified kenaf fiber composite (m-PP/KF) shows the highest improvement in tensile strength compared to CF composites and unmodified composite which is 30.51 MPa. These results were also confirmed by the SEM machine observations of fracture surface of composites and FTIR analysis of the chemical structure. The result of damping analysis showed modified composites with MAPP in 30wt% CF or KF composites lead to good vibration damping which are increased up to 1017.7% and 756.9% compared to neat PP. On the other hand, the 30wt% m- PP/CF and 30wt% m-PP/KF showed the highest delay in first dripping time compared to neat PP which are increased up to 800% and 1000%. As the results, the presence of MAPP helps increasing on the mechanical properties, vibration damping properties and flammability properties of both fibers. The 30wt% kenaf fiber with 3wt% MAPP gives the best result compare to others.